E-mobility in China: Chance or daydream? - Ulrike Tagscherer; Rainer Frietsch (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
China is the fastest growing car market in the world. Both, government and industry alike have high hopes for the paradigm shift in mobility towards electric cars. China's industry might be able to catch up or leap-frog, once electric cars have hit the roads. Taking the question if and how paradigm shifts occur as a starting point, this paper describes and assesses the current policies in electro mobility in China and puts them in relation to China's scientific and technological capabilities. The results show that a huge amount of public funding is involved, though spread over many programs and too many provinces. Though the scientific capabilities seem to be very promising, the tech-nological capabilities - applying science to real-world issues - seem to lag behind. These findings let us conclude that the leap-frogging in mobility might not occur in the way the most optimistic spectators might want to see.
Keywords: 330